Wing Chun’s Chum Kiu Form. A Study in Stability and Mobility - Chaudhuri, Joyotpaul (Revista de Artes Marciales Asiáticas, 2012)
This article analyzes the keys to motion in the second empty-hand form of Wing Chun gongfu: Chum Kiu. The focus is on the proper maintenance of the body’s central axis and its motions, which helps with the development of Wing Chun power and the foundations of delivering that power. The form includes short bridges, stepping, turning, and kicking. The motions are built on the structural foundations created by regular practice of the first form, Siu Lim Tau.